2020
DOI: 10.2351/7.0000115
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dimensional accuracy and tolerances of powder bed based and nozzle based additive manufacturing processes

Abstract: Additive manufacturing processes have the potential to produce near-net shaped complex final parts in various industries such as aerospace, medicine, or automotive. Powder bed based and nozzle based processes like laser metal deposition (LMD), laser powder bed fusion (LPBF), and electron beam melting (EBM) are commercially available, but selecting the most suitable process for a specific application remains difficult and mainly depends on the individual know-how within a certain company. Factors such as the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 10 publications
0
24
0
1
Order By: Relevance
“…To analyze the dimensional accuracy for certain features such as cylinders, overhangs, and walls, a benchmark geometry developed by the Fraunhofer Institute for Material and Beam Technology IWS within the AGENT-3D program was built and analyzed via 3D scanning using an ATOS Core GOM 135 (GOM GmbH, Braunschweig, To analyze the dimensional accuracy for certain features such as cylinders, overhangs, and walls, a benchmark geometry developed by the Fraunhofer Institute for Material and Beam Technology IWS within the AGENT-3D program was built and analyzed via 3D scanning using an ATOS Core GOM 135 (GOM GmbH, Braunschweig, Germany) which can be seen in Figure 2. The geometry and previous measurements with 3D scanning and computed tomography (CT) were described in detail by Lopez et al [24] and Gruber et al [25]. To analyze the dimensional accuracy for certain features such as cylinders, overhangs, and walls, a benchmark geometry developed by the Fraunhofer Institute for Material and Beam Technology IWS within the AGENT-3D program was built and analyzed via 3D scanning using an ATOS Core GOM 135 (GOM GmbH, Braunschweig, Germany) which can be seen in Figure 2.…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the dimensional accuracy for certain features such as cylinders, overhangs, and walls, a benchmark geometry developed by the Fraunhofer Institute for Material and Beam Technology IWS within the AGENT-3D program was built and analyzed via 3D scanning using an ATOS Core GOM 135 (GOM GmbH, Braunschweig, To analyze the dimensional accuracy for certain features such as cylinders, overhangs, and walls, a benchmark geometry developed by the Fraunhofer Institute for Material and Beam Technology IWS within the AGENT-3D program was built and analyzed via 3D scanning using an ATOS Core GOM 135 (GOM GmbH, Braunschweig, Germany) which can be seen in Figure 2. The geometry and previous measurements with 3D scanning and computed tomography (CT) were described in detail by Lopez et al [24] and Gruber et al [25]. To analyze the dimensional accuracy for certain features such as cylinders, overhangs, and walls, a benchmark geometry developed by the Fraunhofer Institute for Material and Beam Technology IWS within the AGENT-3D program was built and analyzed via 3D scanning using an ATOS Core GOM 135 (GOM GmbH, Braunschweig, Germany) which can be seen in Figure 2.…”
Section: Samplesmentioning
confidence: 99%
“…To analyze the dimensional accuracy for certain features such as cylinders, overhangs, and walls, a benchmark geometry developed by the Fraunhofer Institute for Material and Beam Technology IWS within the AGENT-3D program was built and analyzed via 3D scanning using an ATOS Core GOM 135 (GOM GmbH, Braunschweig, Germany) which can be seen in Figure 2. The geometry and previous measurements with 3D scanning and computed tomography (CT) were described in detail by Lopez et al [24] and Gruber et al [25].…”
Section: Samplesmentioning
confidence: 99%
“…One of the main advantages of the LMD process is that in contrast to other processes the excess material is minimized, even though material loss can still be a problem due to overspray of the nozzle [65]. In addition, the deposition rates are higher during LMD, but the overall part quality typically suffers compared to LPBF [66]. The most relevant process parameters for process optimization are powder or wire feed rate, laser power, gas flow and scanning velocity [67].…”
Section: Lmd (Laser Metal Deposition)mentioning
confidence: 99%
“…The accuracy of AM processes is usually assessed by manufacturing of benchmark artifacts [ 1 , 2 , 3 ] with standardized and differently sized geometrical features. For metal powder bed fusion, Gruber et al [ 4 ] showed that the obtained accuracy of the manufactured artifacts could be related to basic process characteristics like beam diameter and layer height. However, also the feedstock material and the quality of the corresponding process parameters strongly affected the results [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…For metal powder bed fusion, Gruber et al [ 4 ] showed that the obtained accuracy of the manufactured artifacts could be related to basic process characteristics like beam diameter and layer height. However, also the feedstock material and the quality of the corresponding process parameters strongly affected the results [ 4 ]. The strong influence of process parameters has also been shown by Smith et al [ 5 ] for the dimensional accuracy of truss structures manufactured by PBF-EB.…”
Section: Introductionmentioning
confidence: 99%